Study of Islamic perspectives of professional code of ethics in the field of computing and informatics - Shuriye, Abdi Omar (Islamic Centre for Research and Development, Australia, 2008)
Muslim Computing Professionals are required by the general will of God to adhere to Islamic worldview; a concept that refers to a comprehensive apprehension of the world especially from a specific standpoint or a personal philosophy of life, it involves creed, culture, attitude and way of thinking. The Islamic worldview as a philosophy for computing professionals is extensive, Shamil, global, ‘Alami, in-depth ‘amiq and harmonizing enterprise of truth, haqul yaqin, and authenticity constructed upon firm faith ‘Aqidah of reality, ‘Ainul yaqin and it advances through the intellect, ‘aql of the believer, Mu’min, and guided rationalism, al-‘aql as-Salim. This denotes that Islamic worldview is a progression model of confederacy of erudition and epistemology; interpretation of actions, the readings of religious teachings and the relations toward others and how a Muslim treat them constitute a vital facet of Islamic worldview, in fact that is the totality of the values by which a Muslim computing professionals should live in. The essential sources of their worldview are the Qur’an and the prophetic traditions. The paper attempts to study the main features of ethical codes of various professional bodies in the field of computing and informatics at the international and national levels. These professional bodies include IEEE-Computer Society, Association of Computing Machinery, British Computer Society, and Institute for the Management of Information Systems, Association of Information Technology Professionals, Canadian Information Processing Society, Australian Computer Society and other bodies. Related principles or codes are selected for evaluation from Islamic perspective to underscore the universality of ethical principles and values that govern diverse professional bodies with varied faiths and cultures in the field, emphasizing the communally promoted principles.